Sunscreen Activity of Fraction n-hexane, Chloroform, and Eethyl Acetate of Ethanol 96% Flamboyan Leaf (Delonix regia. Raf) Extract - Putra Jiwamurwa Pama Tjitda; Febri Odel Nitbani; Maria Kristina Bangko (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
The sunscreen test of fraction n-hexane, chloroform, and ethyl acetate of ethanol 96% flamboyant leaf (Delonix regia. Raf) extract had been performed. This research begins the extraction of a flamboyant leaf using 96% ethanol. Extraction used the maceration method. The extract is fractionation with some solvents such as n-hexane, chloroform, and ethyl acetate. Each fraction was identified secondary metabolite and sunscreen test involving SPF, %Te, and %Tp measurement using UV-Vis Spectrophotometer. The result of phytochemical screening exhibited flavonoids, alkaloids, saponins, tannins, and phenolics in ethyl acetate fraction. n-hexane and chloroform fraction don't show saponins and flavonoid content. The sunscreen test shows that chloroform fraction has good protection power toward UV light with SPF, %Te, and %Tp value is 54.27±0.462, 7.46±0.473, and 12.83±0.047 in 250 mg/L, respectively.